‘Elettra’ abbandonata: quando Giovanni Testori incontrò Franco Parenti - Peja, Laura (Drammaturgia, 2020)
The essay deals with the study of an unpublished dramatic text by Giovanni Testori, Elettra, of which there is a manuscript and two different typed versions, but which the playwright himself let fall into oblivion. Alongside the illustration of the text and its placement in the broad context of contemporary rewritings of the classical myth, the essay proposes a hypothesis of dating to the spring-summer 1970 and widens the perspective to theatrical Italy (in Europe) of the period. This, for the purpose to enlighten the author’s creative work and its development, also made up of breaks, turning points and second thoughts, but consistent in its path towards a theatre that is both popular and ‘visceral’, centred on the concreteness of an actor’s body (as always for the great playwrights of history). A creative itinerary that, perhaps a bit surprisingly, is very much in tune with the theatrical and more widely cultural context of the period, with echoes, intersections and suggestions by Artaud, Brook, Grotowski, Pasolini.